2019
DOI: 10.1085/jgp.201912318
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the transport kinetics of glycine transporter 1 and glycine transporter 2

Abstract: Transporters of the solute carrier 6 (SLC6) family translocate their cognate substrate together with Na+ and Cl−. Detailed kinetic models exist for the transporters of GABA (GAT1/SLC6A1) and the monoamines dopamine (DAT/SLC6A3) and serotonin (SERT/SLC6A4). Here, we posited that the transport cycle of individual SLC6 transporters reflects the physiological requirements they operate under. We tested this hypothesis by analyzing the transport cycle of glycine transporter 1 (GlyT1/SLC6A9) and glycine transporter 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
35
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 48 publications
4
35
1
Order By: Relevance
“…We tested this model by running simulations for three different transport stoichiometries (i.e., Na + /S, 2Na + /S and Na + /Cl − /S in the panels C, D and E, respectively, of Figure 1), and by comparing the resulting concentrations with the calculated values from the thermodynamic equation in Figure 1A. We stress that in these calculations (according to the reaction schemes outlined in panels C, D and E of Figure 1), we assume a hypothetical transporter: In Figure 1 and all subsequent figures, we chose to use rate constants, which describe the GlyT1 [16], but it is obvious that the stoichiometries were varied to an extent, which is not recapitulated by the experimental data for GlyT1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We tested this model by running simulations for three different transport stoichiometries (i.e., Na + /S, 2Na + /S and Na + /Cl − /S in the panels C, D and E, respectively, of Figure 1), and by comparing the resulting concentrations with the calculated values from the thermodynamic equation in Figure 1A. We stress that in these calculations (according to the reaction schemes outlined in panels C, D and E of Figure 1), we assume a hypothetical transporter: In Figure 1 and all subsequent figures, we chose to use rate constants, which describe the GlyT1 [16], but it is obvious that the stoichiometries were varied to an extent, which is not recapitulated by the experimental data for GlyT1.…”
Section: Resultsmentioning
confidence: 99%
“…The equation for the analytical solution can be readily derived in simple schemes like those shown in Figure 2A or Figure 2E, but this becomes substantially more challenging in complex models. However, these complex models, which encompass many additional loops, are required to explain experimental observations [16,19]. Thus, for more complex models, the simulations rather than the analytical solutions are the more practical approach to assess the effect of slippage on the intra- and extracellular substrate concentrations at the steady state.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that GlyT2 but not GlyT1 bound extracellular Na + in a voltage-dependent manner. Voltage jumps from negative (i.e., −60 mV) to more positive potentials, resulted in outwardly directed transient currents, which were presumably carried by dissociating Na + ions ( 20 , 21 ). Our data suggest that the voltage at the membrane settles faster than Na + can unbind.…”
Section: Resultsmentioning
confidence: 99%